Prevalence and Risk Factors of Hepatitis B and Hepatitis C Virus Infections among Patients with Chronic Liver Diseases in Public Hospitals in Addis Ababa, Ethiopia. (3rd January 2013) - Ayele, Abel Girma; Gebre-Selassie, Solomon
Abstract : Background and Aims . Hepatitis B and hepatitis C viruses are major public health problems worldwide. The aim of this study was to determine the prevalence and risk factors of hepatitis B and C virus infections in patients with chronic liver diseases in three public hospitals in Addis Ababa City, Ethiopia. Methods . The study was conducted on 120 clinically diagnosed chronic liver disease patients. Possible associated factors with infections by the viruses were collected from patient using questionnaire. Serum was screened for the presence of hepatitis B surface antigen and antihepatitis C virus antibodies using qualitative immunochromatographic method. Results . Hepatitis B surface antigen was detected in 43 (35.8%) and anti-HCV antibody 27 (22.5%) patients clinically diagnosed to have chronic liver diseases. Hepatitis B virus infection was higher in males 29/76 (38.2%) compared to 14/44 (31.8%) females, while antihepatitis C virus antibody was higher in females 13/44 (29.5%) compared to 14/76 (18.4%) males. Of the study participants, 3 (2.5%) had dual hepatitis B and C virus coinfection. Conclusion . The prevalence of hepatitis B surface antigen and anti-HCV antibody was high in patients below 50 years of age. Dental extraction procedure at health facility was associated with hepatitis C virus infection (OR, 2.95; 95% CI, 1.21–7.17, P = 0.015 ).